Diagnostic and prognostic value of proadrenomedullin in neonatal sepsis - Fahmey, Sameh Samir (Korean J Pediatr, 2018)
PURPOSE: Sepsis is a major cause of neonatal morbidity and mortality. Early diagnosis is a major problem because of the lack of specific clinical signs. Therefore, a reliable diagnostic marker is needed to guide the use of antimicrobial agents. The objective of our study was to assess the value of proadrenomedullin (pro-ADM) in establishing the diagnosis and evaluating the prognosis of neonatal sepsis. METHODS: This study enrolled 60 newborn infants with sepsis proven with positive blood cultures and 30 healthy neonates. Complete blood count, C-reactive protein levels, and pro-ADM levels were obtained from all neonates. RESULTS: The pro-ADM levels were significantly higher (14.39±0.75 nmol/L) in the sepsis group than in the control group (3.12±0.23 nmol/L). The optimal cutoff value for pro-ADM was 4.3 nmol/L, with a sensitivity of 93.3% and a specificity of 86.7%. The pro-ADM levels were also higher in nonsurvivors (P=0.001). CONCLUSION: Pro-ADM can be used as a reliable biomarker for neonatal sepsis. High pro-ADM levels were associated with mortality and could be an early indicator of disease outcome.